Pelatihan Desain Media Pembelajaran Digitas dengan Canva untuk Meningkatkan Kompetensi Mahasiswa PPG Prajabatan PGSD - Setyowati, Yuni; Saleh, Moh (UNIB Press, 2024)
The development of technology in the digital era requires Pre-service PPG (Teacher Professional Education) students to possess competencies in designing creative and innovative digital learning media. This training, attended by 30 students, aimed to enhance their ability to design learning media using Canva. The community service activity was conducted online via Zoom, consisting of three stages: preparation, implementation, and evaluation. The results of the training showed an average post-test score increase of 35%, reflecting the improvement in participants’ competencies. The participants successfully produced engaging and enjoyable digital learning media that support learning at the elementary school level.